The impact of religious and cultural values on the work of NGOs - Shaqoura, Ahmed; Mallem, Youcef (Journal of Human Sciences, 2021)
The concept of non-governmental organizations is considered one of the nomadic or expatriate concepts that move from one cognitive and social environment to another, which may intersect with it or radically differ from it. The problem that we wanted to raise through this article is “to what extent the work of non-governmental organizations is affected by religious and cultural values. And from this auxiliary questions represented in whether non-governmental organizations adhere to the universal values established by various international legislation, such as the Universal Declaration of Human Rights and my conventions. 1966 Concerning political, civil and economic rights, economic, cultural and social rights and other global and regional agreements or commitment to local religious and cultural values in case they conflict.